Investigation of vessel rupture under ultrasound exposure - Lim, Daniel Wei Chun (2017)
High-intensity focused ultrasound has been used to treat cancer and tumors of kidney, breast, liver, bone and pancreas. [1] Local hospitals SGH and KKH had shown that, during the exposure, up to 80% of the vessels were found ruptured. The purpose of this experiment is to investigate vessel rupture under ultrasound exposure. In this study, parameters used were the optimum to create optically opaque in the phantom gel. Three different point focal area were pre set, and they are classified into Set “A”, Set “B” and Set “C”. To increase the accuracy of this investigation, all the unwanted layer on the porcine artery were cut and remove until the tunica adventitia layer is reached. Both High Intensity Focused Ultrasound transducer and phantom gel model were secured to the three axis positioning system to achieve precise movement during the adjustment of ultrasound focal point on the artery. The porcine artery used was cut to an average length of 50mm. Each piece of artery will receive 6 to 8 times trigger cycle from the focused ultrasound and the focal point were spaced 5mm from each other. By doing so, optimum usage and results could be retrieved from each piece of artery used. Lesions were created by the focused ultrasound in a phantom gel (without artery), this serves as a benchmark for other lesion created with embedded artery. Results from all 3 different Sets of focal point shows reduction in lesion size and opacity, which is a clear sign of acoustic energy loss. Thermal absorption could also be seen from all 3 different sets of focal point, as the pinkish involuntary muscle fiber degrade and cause a visible discoloration to a brownish colour. Mechanical effect caused by the focused ultrasound could also be visible under the observation’s high speed images. Both Set “A” and Set “B” have visible breakage on the surface of the artery. The most significant discoloration and surface pocket indentation on the artery could been seen on Set “B”. But results from all 3 different focal points showed damage caused by the focused ultrasound but did not had the full capability of creating a puncture on it, which will then cause a rupture.